2018
DOI: 10.1002/adfm.201804197
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Metal Droplets Wrapped with Polysaccharide Microgel as Biocompatible Aqueous Ink for Flexible Conductive Devices

Abstract: Nanometerization of liquid metal in organic systems can facilitate deposition of liquid metals onto substrates and then recover its conductivity through sintering. Although having broader potential applications, producing stable aqueous inks of liquid metals keeps challenging because of rapid oxidation of liquid metal when exposing to water and oxygen. Here, a biocompatible aqueous ink is produced by encapsulating alloy nanodroplets of gallium and indium (EGaIn) into microgels of marine polysaccharides. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
225
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(228 citation statements)
references
References 39 publications
3
225
0
Order By: Relevance
“…Nanosized distribution in bulk solids has been very difficult for liquid metals due to their unique physical interfacial energy. [22] As shown in Figure 3b (Figure 3c), which exhibited heavily phase separation in 1 h. [8] Transmission electron micro scopy (TEM) image of the LM colloidal solution (Figure S11, Supporting Information) showed that the polysulfide loops and thiol groups in sulfur polymers significantly helped the dispersion of liquid metals in solution, achieving an average size as small as 82 nm, similar as previous reports. [31][32][33][34][35] In this work, ring-opening polymerization and inverse vulcanization of elemental sulfur offer sufficient polysulfide loops and thiol ligand (Scheme S1; Figure 2b,c) to disperse the liquid metals.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Nanosized distribution in bulk solids has been very difficult for liquid metals due to their unique physical interfacial energy. [22] As shown in Figure 3b (Figure 3c), which exhibited heavily phase separation in 1 h. [8] Transmission electron micro scopy (TEM) image of the LM colloidal solution (Figure S11, Supporting Information) showed that the polysulfide loops and thiol groups in sulfur polymers significantly helped the dispersion of liquid metals in solution, achieving an average size as small as 82 nm, similar as previous reports. [31][32][33][34][35] In this work, ring-opening polymerization and inverse vulcanization of elemental sulfur offer sufficient polysulfide loops and thiol ligand (Scheme S1; Figure 2b,c) to disperse the liquid metals.…”
Section: Introductionsupporting
confidence: 84%
“…[15,17] The polysulfide loops (R-S n -R) and thiol terminal groups (R-SH) are both very effective ligands to stabilize liquid metals in solution as reported by previous references (Figure 3a). [8,9] The X-ray photoelectron spectroscopy (XPS) spectra (Figure 3d; Figure S13, Supporting Information) for liquid metals collected from LMESP-50% solution showed peaks of Ga 2d, Ga 3d, In 3d, O 1s, C 1s, and S 2p, indicating the coating (binding) of sulfur polymers on LM. [22] As shown in Figure 3b (Figure 3c), which exhibited heavily phase separation in 1 h. [8] Transmission electron micro scopy (TEM) image of the LM colloidal solution (Figure S11, Supporting Information) showed that the polysulfide loops and thiol groups in sulfur polymers significantly helped the dispersion of liquid metals in solution, achieving an average size as small as 82 nm, similar as previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been well‐studied and the resulting colloidal solution was employed as conductive ink for soft and flexible electronics . Stable aqueous suspensions of LM nanodroplets are not only for electronic applications, but also exhibit great potential in medicine and therapy, such as drug delivery, photothermal therapy, and bioimaging . Water‐soluble surfactants, including cetrimonium bromide, poly(4‐vinyl‐1‐methyl‐pyridinium bromide), lysozyme, and trithiocarbonate‐functionalized brushed polyethylene glycol have been used to stabilize LM nanodroplets during and after sonication of bulk LMs in water .…”
mentioning
confidence: 99%
“…Water‐soluble surfactants, including cetrimonium bromide, poly(4‐vinyl‐1‐methyl‐pyridinium bromide), lysozyme, and trithiocarbonate‐functionalized brushed polyethylene glycol have been used to stabilize LM nanodroplets during and after sonication of bulk LMs in water . In addition, when LM nanodroplets in aqueous solution are placed at room temperature for 16 h or heated up to about 70 °C for 30 min, the spherical nanodroplets will be oxidized and dealloyed, resulting in the formation of rods of gallium oxide monohydroxide (GaOOH) and spherical indium nanoparticles . To overcome this issue, various polymer coatings were used to inhibit the oxidation of LM nanodroplets and stabilize them .…”
mentioning
confidence: 99%
“…), which is enabled to slightly elongate but it is also limited. [20][21][22][23][24][25] In their methods, the liquid metal has been designed into functional conductive structure by taking advantage of own liquid characteristic. [15,16] Unlike these traditional conductive rigid materials, the emerging galliumbased liquid metals with advantages of low Young's moduli (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and in principle infinitely deformable have attracted great attention as an ideal candidate for fabricating stretchable conductive pattern.…”
mentioning
confidence: 99%